Discontinuous transmission and multiplexing - Shah, Asadullah; Shaikh, Muniba (IIUM Press, 2011)
Discontinuous Transmission (DTX) is a concept used in some mobile standards, mostly in Groupe Special Mobile (GSM) systems. In DTX systems, Voice Activity Detection (VAD) and comfort noise are essential element. The usage of DTX in the systems allo\vs transmissions during activity periods and remains silent during non-activities. This chapter is dedicated for DTX and VAD, their usage in STDM designs